A two-channel thermal dissociation cavity ring-down spectrometer for the detection of ambient NO2, RO2NO2 and RONO2 - Thieser, Jim; Schuster, G.; Schuladen, J.; Phillips, G. J.; Reiffs, A.; Parchatka, U.; Pöhler, Denis; Lelieveld, J.; Crowley, J. N. (Atmospheric measurement techniques, 2016)
Abstract. We describe a thermal dissociation cavity ring-down spectrometer (TD-CRDS) for measurement of ambient NO2, total peroxy nitrates (ΣPNs) and total alkyl nitrates (ΣANs). The spectrometer has two separate cavities operating at ∼ 405.2 and 408.5 nm. One cavity (reference) samples NO2 continuously from an inlet at ambient temperature, the other samples sequentially from an inlet at 473 K in which PNs are converted to NO2 or from an inlet at 723 K in which both PNs and ANs are converted to NO2, difference signals being used to derive mixing ratios of ΣPNs and ΣANs. We describe an extensive set of laboratory experiments and numerical simulations to characterise the fate of organic radicals in the hot inlets and cavity and derive correction factors to account for the bias resulting from the interaction of peroxy radicals with ambient NO and NO2. Finally, we present the first measurements and comparison with other instruments during a field campaign, outline the limitations of the present instrument and provide an outlook for future improvements.